Acute and subacute (28 days) oral toxicity assessment of the oil extracted from Acrocomia aculeata pulp in rats - Traesel, Giseli Karenina; Souza, Juliane Coelho de; Barros, Aline Lima de [UNESP]; Souza, Marcos Alexandre; Schmitz, Wanderley Onofre; Muzzi, Rozanna Marques; Oesterreich, Silvia Aparecida; Arena, Arielle Cristina [UNESP] (Elsevier B.V., 2014)
Acrocomia aculeata, popularly known as "bocaitiva", is a species used for nutritional purposes and for the treatment of various diseases, as it has, among other things, high levels of antioxidant compounds. This study aimed to assess the toxicological profile of A. aculeata, through acute and subacute toxicity tests. Male and female rats (Wistar) received by gavage 2000 mg/kg of oil extracted from the pulp of A. aculeata (OPAC) for the acute toxicity test and 125, 250, 500 or 1000 mg/kg of OPAC for subacute toxicity test. In the acute toxicity study no mortality or behavioral changes were observed in rats treated with 2000 mg/kg, indicating that the LD50 is higher than this dose. In the subacute toxicity test, the tested doses produced no significant changes in hematological, biochemical or histopathological parameters in the animals exposed. These results demonstrate the absence of acute and subacute toxicity after oral exposure to A. aculeata oil in rats. However, further studies in animals and in humans are needed in order to have sufficient safety evidence for its use in humans. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Acrocomia aculeata; Acute toxicity; Subacute toxicity; Safety; Rats